Development prospects for physical therapy in health care of Ukraine. - Kobelyev S.Y (Kharkov National Pedagogical University, 2011)
Made a comparative analysis of systems restore therapy in Ukraine and abroad. It is considered the features of functioningof service remedial gymnastics and physical therapy. Emphasized on the main differences of education physician, assistant of remedial gymnastics and physical therapist. In the context of integration processes correctly and expediently in place Service remedial gymnastics to apply the modern direction physical therapy. Specified the need to reorganize the health system of Ukraine, on the legislative and local levels.